Crushing tablets or sprinkling capsules: Implications for clinical strategy and study performance based on BE studies of rivaroxaban and deferasirox - Sus, Jan; Bosak, Jan; Hauser, Tomas (Clinical and translational science, 2024)
Administration of oral medicinal products as crushed tablets or open capsules is an important delivery option for patients suffering from dysphagia. To obtain full interchangeability of generics with the original products, demonstration of bioequivalence (BE) between both products administered as crushed tablets/open capsules was required for poorly soluble product by European Medicines Agency (EMA) at the time of development of our rivaroxaban and deferasirox generic products. We present the results of two BE studies with modified administration of these products, which compared relative bioavailability between generic and reference products. In the rivaroxaban study, the test product was administered as a capsule sprinkled on and mixed with applesauce, whereas the reference tablet was crushed and administered with applesauce under fed conditions. In the deferasirox study, both treatments were administered as crushed tablets under fasting conditions. Both studies applied a two-way crossover design and were conducted after a single-dose in healthy volunteers. The 90% confidence interval of the geometric mean ratio area under the analyte concentration versus time curve, from time zero to the time of the last measurable analyte concentration and maximum measured analyte concentration over the sampling period of the test to reference ratio were 103.36-110.37% and 97.98-108.45% for rivaroxaban, respectively, and 96.69-107.29% and 94.19-109.45% for deferasirox, respectively. Thus, the BE criteria (80.00-125.00%) were met in both studies which demonstrated that bioavailability was not affected when the test and reference products were administered in the form of crushed tablet/open capsule. These results support the argument of redundancy of crushed product studies for poorly soluble drugs, which is in line with the currently revised position of the EMA on this topic.
Keywords: Deferasirox; lidé; generika; Administration, Oral; terapeutická ekvivalence; Rivaroxaban; Tablets; Therapeutic Equivalency; aplikace orální; rivaroxaban; deferasirox; tablety; Drugs, Generic; Humans